Peran Puskesmas Sumberasih Dalam Pembinaan KP-ASI Sebagai Upaya Pencegahan Stunting Di Desa Banjarasari Kabupaten Probolinggo - Ananta Prathama; Indira Nurdivanuha; Thirza Abrina Damayanti; Aisha Dwi Agustina; Tarisa Dwitasari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The issue of stunting is still a hot topic of conversation in society. Impacts on children's growth and development can arise if they experience stunting or failure to thrive. Therefore to overcome these problems can be done by focusing on the First 1000 Days of Life (HPK) group which involves pregnant women, nursing mothers, and children aged 0-23 months. Through the 1000 HPK Group coaching program, the understanding of pregnant women and breastfeeding mothers will increase. The methods used include the observation method through observing the course of activities and noting important parts in KP-ASI coaching activities and documenting these activities, the interview method through confinement or counseling sessions about what problems are faced by pregnant women and breastfeeding mothers, the method of literature review through pre -test and post-test to determine the extent of understanding of prospective mothers or pregnant women and nursing mothers. The results of this activity show that the understanding of pregnant women and breastfeeding mothers in Banjar Utara Hamlet, Banjarsari Village about exclusive breastfeeding increased from 58% to 87%.